Putusan Hakim dalam Penetapan Perkara Dispensasi Nikah yang tidak Diterima Perspektif Maqashid Syariah (Studi Kasus Nomor 186/Pdt.P/2023/PA.Kng) - Hidayat, Yayat; Madinah, Dina; Islamiati, Annisa (AL-MASHALIH (Journal of Islamic Law), 2024)
The number of marriage dispensation cases at the Kuningan Religious Court is very high. Of the 2,579 marriage dispensation cases per year from 2020 to 2024, there were 1,282 cases accepted by the Kuningan Religious Court and 1,297 cases were not accepted by the Kuningan Religious Court. The high number of marriage dispensation cases at the Kuningan Religious Court makes this research important to conduct. This study aims to determine the judge's decision on case Number 186/Pdt.P/2023/PA.Kng regarding the application for marriage dispensation, and to analyze the maqashid sharia review of the judge's decision on case Number 186/Pdt.P/2023/PA.Kng regarding the application for marriage dispensation. The research method used in this study is a qualitative research method with a combined research type, namely field research and library research. In addition, the data collection techniques used in this study were structured interviews and documentation. The results of this study found that the decision of the Kuningan Religious Court judge in determining the marriage dispensation case in case study Number 186/Pdt.P/2023/PA.Kng was not accepted because the prospective husband's biological father was not present at the trial. The judge's decision regarding the application for marriage dispensation that was not accepted in case Number 186/Pdt.P/2023/PA.Kng is not in accordance with the concept of maqashid sharia. The positive legal basis used by the judge in considering the decision does have benefits. However, many things are then neglected according to sharia or maqashid so that the harm caused is greater than the benefits.